Identificación y selección de rizobacterias del género pseudomonas spp de cultivares endémicos de musa spp con actividad antagonista al hongo mycosphaerella fijiensis. - Chávez Arteaga, Karen Tatiana (2016)
The constant application of fungicides for the control of M. fijiensis, has caused this pathogen to acquire resistance. The use of biocontrol in agriculture offers an alternative to benefit aspects physiological and at the same time reducing the use of agrochemicals. This study aimed to identify native Pseudomonas spp. rhizobacteria by morphological and biochemical characters of antagonist activity towards the fungus. A set of 50 strains provinces Los Ríos (Quinsaloma and Patricia pillar), Cotopaxi (La Mana) and Bolivar (the ships), which were inoculated for their morphological traits analyzed. The colonies that emitted fluorescence were selected and analyzed for protease detection and identification of antibiotic cyanide in hydrogen (HCN). The supernatants were obtained through the process of centrifugation proteolytic strains. For the isolation of M. fijiensis was carried out downloads of ascospores to the production of crop monoascosporicos. We studied a single factor, rhizobacteria, three trials were conducted: 1) antagonist assay of germination of M. fijiensis ascospores, germination percentage was determined by counting 10 ascospores per 0.5 cm2; ((2) trial evaluated by absorbance at the Mycelial growth of M. fijiensis, antagonists was a concentration of Mycelial fragments, and evaluated the effect of the supernatants on Mycelial growth to 10% y3) antagonist inhibition test of diameter growth of mycelium M. fijiensis, with the evaluation of growth inhibition was assessed at 10% of the supernatant. The design was used completely lift (D.C.A) to evaluate the antagonistic effect of rhizobacteria, Duncan's test was used to 95%. Results of 20 strains that emitted fluorescence is obtained, eight strains were proteolytic and five were the identification of HCN. The p. protegens CHA0 and p. fluorescens PM3-8 showed more antagonistic activity towards M. fijiensis in all evaluated trials.